American Engineering Council Records Appreciation of Herbert Hoover - AIME AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1921)
T HE Executive Board of the American Engineering Council held its fourth meeting at St. Louis on the first anniversary of the organizing conference which met in Washington on June 3,1920. Representatives of a number of the leading engineering organizations in the vicinity of St. Louis were present by invitation. The members of the Executive Board were guests of the Associated Engineering Societies of St. Louis. They were given a delightful ride about the city and were entertained at the Glen Echo Country Club at dinner. The special committee that had been appointed to draft resolutions to Mr. Hoover submitted the following, which were adopted : WHEREAS, our President, Herbert Hoover, has been appointed Secretary of Commerce in the Cabinet of the President of the United States, and WHEREAS, in consequence of his acceptance of this high public office, he has deemed it necessary to tender his resignation as President of The Federated American Engineering Societies.